Tn Antigen Expression Contributes to an Immune Suppressive Microenvironment and Drives Tumor Growth in Colorectal Cancer - Cornelissen, Lenneke A. M.; Blanas, Athanasios; Zaal, Anouk; van der Horst, Joost C.; Kruijssen, Laura J. W.; O’Toole, Tom; van Kooyk, Yvette; van Vliet, Sandra J. (Frontiers in Oncology, 2020)
Expression of the tumor-associated glycan Tn antigen (αGalNAc-Ser/Thr) has been correlated to poor prognosis and metastasis in multiple cancer types. However, the exact mechanisms exerted by Tn antigen to support tumor growth are still lacking. One emerging hallmark of cancer is evasion of immune destruction. Although tumor cells often exploit the glycosylation machinery to interact with the immune system, the contribution of Tn antigen to an immunosuppressive tumor microenvironment has scarcely been studied. Here, we explored how Tn antigen influences the tumor immune cell composition in a colorectal cancer (CRC) mouse model. CRISPR/Cas9-mediated knock out of the C1galt1c1 gene resulted in elevated Tn antigen levels on the cell surface of the CRC cell line MC38 (MC38-Tnhigh). RNA sequencing and subsequent GO term enrichment analysis of our Tnhigh glycovariant not only revealed differences in MAPK signaling and cell migration, but also in antigen processing and presentation as well as in cytotoxic T cell responses. Indeed, MC38-Tnhigh tumors displayed increased tumor growth in vivo, which was correlated with an altered tumor immune cell infiltration, characterized by reduced levels of cytotoxic CD8+ T cells and enhanced accumulation of myeloid-derived suppressor cells. Interestingly, no systemic differences in T cell subsets were observed. Together, our data demonstrate for the first time that Tn antigen expression in the CRC tumor microenvironment affects the tumor-associated immune cell repertoire.